An Evaluation of El Real Decreto Ley 9/2021 The Spanish Royal Decree Accepting Delivery Platform Couriers as Employees - Burcu Ezer (İstanbul Hukuk Mecmuası)
Discussions on working via digital platforms and the legal status of those working on digital platforms have become two significant issues in recent years. The fact that these emerging new work relations differ from traditional dependent labor relations has led to the emergence of different views on the legal status of platform workers. For various sociocultural and economic reasons, platform work has gained widespread popularity in Spain in a short time compared to most European countries, with Spain ranking as the European country with the highest ratio of workers working on digital platforms out of the overall working age population in recent years. Of these digital platforms, delivery platforms are some of the most common. Through the effects of their prevalence, the legal status of delivery platform workers has become a significant issue in Spanish Law. In particular, resolving the issue of rulings that go in different directions regarding the legal status of delivery platform couriers has become necessary with the decision on the unification of conflicting judgments. In 2020, the Spanish Supreme Court ruled that delivery platform couriers have the status of employees under SpanishLaw. Following this ruling, a disputable presumption was added to Workers Law No. 2/2015 by Spanish Royal Decree No. 9/2021. Furthermore, employers and platforms that use algorithms to regulate working conditions are obliged to inform workers’ representatives about which algorithms are used. With this change in law, Spain became the first European country to accept delivery platform couriers as employees through a legal regulation. This study will first cover the Spanish Supreme Court’s ruling to unify jurisprudence and then examine the regulations enacted by Spanish Royal Decree No. 9/2021.